Primary testicular follicular lymphoma - Sofia Garces; Jie Xu; Shaoying Li (Elsevier, 2022)
Background: Primary testicular follicular lymphoma (TFL) is a rare extranodal variant of follicular lymphoma confined to the testis, almost exclusively occurring in children and young adults. TFL has unique clinicopathologic features and excellent prognosis. Distinction of TFL from other neoplasms involving testis and from systemic follicular lymphoma is essential due to major differences in management and outcome. Aim: We aimed to review and summarize the existing literature describing clinical, histopathologic, immunophenotypic and genetic features of TFL. We also include distinguishing characteristics of potential morphologic mimickers of TFL, including usual follicular lymphoma involving the testis as part of systemic disease. Methods: PubMed was searched for relevant studies before December 1, 2021, using keywords "primary testicular lymphoma", "primary testicular follicular lymphoma" and "follicular lymphoma". We selected and summarized the results of relevant studies. We also reviewed the latest WHO Classification of Tumors of Hematopoietic and Lymphoid Tissues. Conclusions: Primary testicular follicular lymphoma (TFL) is a unique extranodal variant of follicular lymphoma mainly presenting in children and young adults as stage 1E disease. Microscopically, TFL has a follicular or follicular and diffuse growth pattern and is composed predominantly of centroblasts. TFL characteristically lacks the t(14;18)/IGH-BCL2 and BCL2 protein overexpression. Optimal management is not well defined. Nevertheless, after unilateral orchiectomy combined with chemotherapy, TFL has shown excellent prognosis without recurrence. A focal diffuse large B-cell component does not appear to confer adverse prognosis.